The study of language - Yule, George, 1947- (Cambridge University Press, 2014)
"This bestselling textbook provides an engaging and user-friendly introduction to the study of language. Assuming no prior knowledge of the subject, Yule presents information in bite-sized sections, clearly explaining the major concepts in linguistics - from how children learn language to why men and women speak differently, through all the key elements of language. This fifth edition has been revised and updated with new figures and tables, additional topics, and numerous new examples using languages from across the world. To increase student engagement and to foster problem-solving and critical thinking skills, the book includes thirty new tasks. An expanded and revised online study guide provides students with further resources, including answers and tutorials for all tasks, while encouraging lively and proactive learning. This is the most fundamental and easy-to-use introduction to the study of language"--Resumé vydavatele
Předchozí vydání: 2010
Keywords: jazyk; lingvistika; studium jazyků; language; linguistics; language learning; učebnice vysokých škol; textbooks (higher)